2004
DOI: 10.1002/anie.200300645
|View full text |Cite
|
Sign up to set email alerts
|

The 2×3 Toolbox of Organometallic Methods for Regiochemically Exhaustive Functionalization

Abstract: This review describes a concept aimed at rational and maximal structure proliferation. To this end, simple aromatic or heterocyclic starting materials, often bulk chemicals, are converted into all regionisomerically possible polar organometallic intermediates (mostly lithiated species), which then may be combined with any of the countless electrophiles to provide attractive new building blocks, particularly functionalized derivatives. The practical implementation relies on a set ("toolbox") of sophisticated re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
43
0
4

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 285 publications
(47 citation statements)
references
References 101 publications
0
43
0
4
Order By: Relevance
“…While the metallation reaction remains an essential tool for constructing substituted aromatic compounds [1–2], the quest for new improved reagents capable of selectively abstracting hydrogen from organic substrates continues. Routinely, organolithium reagents have been employed for this purpose with the high electropositivity of lithium affording polar, reactive C δ− –Li δ+ bonds proficient in metallating C–H bonds in organic, especially aromatic and heteroaromatic, compounds [3–5].…”
Section: Introductionmentioning
confidence: 99%
“…While the metallation reaction remains an essential tool for constructing substituted aromatic compounds [1–2], the quest for new improved reagents capable of selectively abstracting hydrogen from organic substrates continues. Routinely, organolithium reagents have been employed for this purpose with the high electropositivity of lithium affording polar, reactive C δ− –Li δ+ bonds proficient in metallating C–H bonds in organic, especially aromatic and heteroaromatic, compounds [3–5].…”
Section: Introductionmentioning
confidence: 99%
“…[2] Gewçhnlich stellt das Vorhandensein einer dirigierenden Gruppe die Lithiierung in der ortho-Position sicher,i mF all von unsymmetrischen Substraten von Typ 1 kann allerdings ein Gemisch der regioisomeren Aryllithiumverbindungen 2 und 3 erhalten werden. [3] Die Bildung solcher Gemische erschwert die Anwendungen in Synthesen ungemein. Das Problem fehlender Regioselektivität kçnnte mçglicherweise durch eine bevorzugte Tr ansmetallierung eines der beiden Regioisomere 2 und 3 gelçst werden.…”
Section: Organolithiumreagentien Sind Wichtige Metallorganischeunclassified
“…Polar organometallic chemistry [3335] allows the performance of highly selective reactions. Therefore, it seemed to us the ideal tool to reaching this goal.…”
Section: Introductionmentioning
confidence: 99%
“…Although this reaction was reported by C. S. Marvel in 1927 [40], G. Wittig [41] and H. Gilman [4244] were the first to apply it in organic synthesis in the late thirties. Since then, this reaction has been considered as a mature method lacking both appeal and surprise [33], and only new applications of this reaction or mechanistic studies have been reported [30,3233 4555]. However, in the last few years, the halogen–metal permutation has recaptured its former role as one of the most important and versatile methods in organic synthesis.…”
Section: Introductionmentioning
confidence: 99%